Impact of gestational and lactational phthalate exposure on hypothalamic content of amino acid neurotransmitters and FSH secretion in peripubertal male rats - Carbone, Silvia Elena (2010)
This study investigated the effect of the pre- and perinatal exposure to di-(2-ethylhexyl) phthalate (DEHP) on the neuroendocrine parameters that regulate reproduction in peripubertal male rats. DEHP at dose of 3 and 30 mg/kg. bw/day was administered orally to female rat since pregnancy onset until weaning. The male litters were sacrificed at 30 days of age to determine gonadotropin serum level and the hypothalamic contents of the amino acids aspartate and gamma-aminobutyric acid. No changes in gonadotropin, aspartate and gamma-aminobutyric acid levels were detected at the low dose. DEHP 30 mg/kg. bw/day reduced testis weight and serum FSH, in correlation with a significant increase in the inhibitory GABAergic tone and a reduction in the stimulatory effect of aspartate on gonadotropin level. This study provides unknown data regarding changes in the hypothalamic contents of the amino acid neurotransmitters, which are involved in the neuroendocrine regulation of reproductive axis, in peripubertal male rat offspring from dams exposed to DEHP during gestational and lactational periods. This could be related with the gonadotropin modifications also here described.